2017
DOI: 10.1103/physrevb.96.045436
|View full text |Cite
|
Sign up to set email alerts
|

Quantum electron transport in magnetically entangled subbands

Abstract: Transport properties of highly mobile 2D electrons in symmetric GaAs quantum wells with two populated subbands placed in titled magnetic fields are studied at high temperatures. Quantum positive magnetoresistance (QPMR) and magneto-intersubbands resistance oscillations (MISO) are observed in quantizing magnetic fields, B ⊥ , applied perpendicular to the 2D layer. QPMR displays contributions from electrons with considerably different quantum lifetimes, τ (1,2) q , confirming the presence of two subbands in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…2. In contrast to the regular quantum wells with two populated subbands [30][31][32] , these two conducting 2D layers are separated from each other and do not interact. This is supported by the fact, that the magneto-inter-subband oscillations, induced by the electron inter-subband scattering 30,33,34 , are absent in the studied system.…”
Section: Modelmentioning
confidence: 99%
“…2. In contrast to the regular quantum wells with two populated subbands [30][31][32] , these two conducting 2D layers are separated from each other and do not interact. This is supported by the fact, that the magneto-inter-subband oscillations, induced by the electron inter-subband scattering 30,33,34 , are absent in the studied system.…”
Section: Modelmentioning
confidence: 99%
“…It was shown that they are described by linear dependences, and the quantities τ q1 and τ q2 , which are calculated from their slope, are significantly different. Dingle plots for MIS oscillations were studied only in GaAs quantum wells with AlAs/GaAs lateral superlattice barriers [19][20][21][22]. It was also established that the dependences on 1/ in such heterostructures at K are nonlinear.…”
Section: Condensed Mattermentioning
confidence: 99%
“…The value in this case is mainly determined by the width of the quantum well. The classical positive magnetoresistance is manifested in the narrow quantum well in the fields of T [20]; the MIS oscillations then follow, which coexist with SdH oscillations in the fields T. An insignificant modulation of the amplitude of MIS oscillations in the range from 0.1 to 0.5 T is associated with the interference of magnetophonon and MIS oscillations [25,26]. The Fourier analysis of such dependences gives three frequencies corresponding to the periods of SdH oscillations in the first and second subbands, as well as the period of MIS oscillations.…”
Section: Condensed Mattermentioning
confidence: 99%
“…Recently we have studied transport properties of high quality GaAs quantum wells with two populated subbands in a tilted magnetic fields. 16 The goals of that study were to detect effects of the spin (Zeeman) splitting on MISO, which has not been seen before as well as to investigate the effect of the spin splitting on quantum positive magnetoresistance (QPMR) [17][18][19][20] in a 2D system with two populated subbands . These experiments have demonstrated a significant reduction of the QPMR with the application of the in-plane magnetic field, which was in good agreement with the modification of the electron spectrum via Zeeman effect with g-factor g ≈0.43±0.07.…”
Section: Introductionmentioning
confidence: 99%